Case Study of Collaboration Skills and Learning Outcomes of High School Students on Physics Learning in Global Warming Materials - Noviana, RA Rasania; Wiyono, Ketang; Marlina, Leni (Indonesian Journal of Education Research (IJoER), 2024)
Purpose of the study: Describe the influence of collaboration skills on the learning outcomes of global warming concepts for students at Alumnika Sains High School Palembang. Methodology: This type of research uses a qualitative descriptive method that aims to provide a description of collaboration skills and student learning outcomes in physics learning on global warming material. Data collection techniques in this research include direct observation, using research instruments in the form of rubric sheets and self-assessment collaborative research questionnaires. Main Findings: The results show that if the significance value of the correlation test is 0.752, which is greater than the general significance threshold value which is set at 0.05, then the conclusion is that there is no significant relationship between collaboration skills and learning outcomes of students in the sample. Novelty/Originality of this study: Adding a new perspective on how collaboration skills may not always be significantly correlated with learning outcomes on specific concepts such as global warming in Indonesian high school environments, provides an opportunity to explore other variables that may be more influential.